Argument structure representation and theory - Freeman, James B. (Argumentation library, 2011)
This monograph presents a method of diagramming argument macrostructure, synthesizing the standard circle and arrow approach with the Toulmin model. A theoretical justification of this method through a dialectical understanding of argument, a critical examination of Toulmin on warrants, and a thorough discussion of the linked-convergent distinction follows. Discussion includes consideration of alternative understandings of  argument structure and its representation presented in Wigmore?s chart method, Pollock?s inference graphs, and the pragma-dialectical approach to argumentation. An account of the proper reconstruction of enthymemes and issues at the border of structural analysis versus evaluation of arguments conclude the book.